Next-generation tobacco and nicotine products: Substantiating harm reduction and supporting tobacco regulatory science. (4th May 2018) - Peitsch, Manuel C; Polosa, Riccardo; Proctor, Christopher; Hassler, Thord; Gaca, Marianna; Hill, Erin; Hoeng, Julia; Hayes, A Wallace
A framework for the assessment of novel next-generation tobacco and nicotine products with the potential to reduce health risks compared with cigarettes should integrate scientific studies incorporating nonclinical, clinical, and population studies approaches. These products should have lower emissions and exhibit reduced biological effects compared with those of cigarettes, ideally approaching those of smoking cessation. The products should also be acceptable cigarette alternatives for current smokers, while not appealing to nonsmokers or former smokers. Validating harm reduction and promoting regulatory acceptance of the assessment methods require a collaborative approach by industry, independent reviewers, the public health community, and regulatory agencies. This article summarizes the science and approaches applied and considered to substantiate tobacco harm reduction in the light of regulatory requirements, presented at the 53rd Congress of the European Societies of Toxicology, 2017.